Structural, Optical, and Magnetic Properties of Zn-Doped CoFe(2)O(4) Nanoparticles - Tatarchuk, Tetiana (Nanoscale Res Lett, 2017)
The effect of Zn-doping in CoFe(2)O(4) nanoparticles (NPs) through chemical co-precipitation route was investigated in term of structural, optical, and magnetic properties. Both XRD and FTIR analyses confirm the formation of cubic spinel phase, where the crystallite size changes with Zn content from 46 to 77 nm. The Scherrer method, Williamson-Hall (W-H) analysis, and size-strain plot method (SSPM) were used to study of crystallite sizes. The TEM results were in good agreement with the results of the SSP method. SEM observations reveal agglomeration of fine spherical-like particles. The optical band gap energy determined from diffuse reflectance spectroscopy (DRS) varies increases from 1.17 to 1.3 eV. Magnetization field loops reveal a ferromagnetic behavior with lower hysteresis loop for higher Zn content. The magnetic properties are remarkably influenced with Zn doping; saturation magnetization (M(s)) increases then decreases while both coercivity (H(C)) and remanent magnetization (M(r)) decrease continuously, which was associated with preferential site occupancy and the change in particle size.